Septic pyomyositis, multiple pelvic osteomyelitis and thrombosis in a Thoroughbred foal. (3rd October 2018) - Pressanto, M. C.; Beccati, F.; Stefanetti, V.; Passamonti, F.; Pilati, N.; Pepe, M.
Summary: Multiple septic osteomyelitis, septic thrombi and septic arthritis are recognised as possible complications of sepsis; however, there are few reports of localised pyomyositis in association with septic arterial thrombosis in foals. A 1‐month Thoroughbred colt was presented for investigation of acute and progressive left hindlimb lameness. Physical and laboratory examinations were performed. Ultrasonographic, radiographic and computed tomographic examinations revealed the presence of multiple abscesses and areas of osteomyelitis localised to the gluteal muscles, coxal bone and lumbar spine respectively. Considering the poor prognosis, the foal was subjected to euthanasia. Necropsy confirmed the diagnostic imaging findings and revealed the presence of an extensive septic thrombus, affecting the internal iliac artery, and a single pulmonary abscess. Streptococcus equi subsp. zooepidemicus was isolated from all lesions.